Practitioner's Guide to Effective Maritime and Port Security - Edgerton, Michael (Hoboken, N.J. : Wiley, 2013)
Sets forth practices to ensure security and foster international trade Written with an international perspective, this book analyzes the complex set of factors affecting the security of port and maritime operations, including shipping, politics, economics, crime, and terrorism. Author Michael Edgerton critiques current approaches to maritime and port security based on his more than twenty-five years of experience in the field. He not only points out vulnerabilities in today's practices, but also provides a set of proven and tested recommendations that recognize the role and int.
Tendency Towards Risk Aversion or AvoidanceFocus on Risk Mitigation (Reduction) instead of Risk Treatment; Lack of Recognition of Critical Nodes in the Maritime Domain; Overquantifying Security Risk; Tendency to Use the Rubric of All-hazard Risk; A Propensity to Minimize the Element of Threat in Performing Security Risk Assessments; CHAPTER 5 A Critique of Current Maritime Security Measures and Approaches; Introduction; Regulations and Their Limits; The ISPS Code; Supply Chain Security; International Organization for Standardization.
Includes bibliographical references and index.
Print version record.
Keywords: Harbors -- Security measures; Shipping -- Security measures; Maritime terrorism -- Prevention; Harbors -- Security measures -- United States; Shipping -- Security measures -- United States; Maritime terrorism -- United States -- Prevention; BUSINESS & ECONOMICS -- Infrastructure; SOCIAL SCIENCE -- General; Technology; Electronic books